Haiti : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Augmentation of Access and Waiver of Nonobservance of Performance Criteria, and Request for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report ;, 2008)
This paper discusses key findings of the Third Review Under the Poverty Reduction and Growth Facility (PRGF) for Haiti. Despite external shocks, program performance was solid in the first half of FY2008, with all but one quantitative performance criteria (PC) met. Most structural conditionality was also met on time, although two PCs require waivers. The authorities' revised program through end-September is based on a policy response that balances adjustment and financing, and safeguards macroeconomic stability. IMF staff supports the authorities' response to the shocks.